Advances in Mesoporous Silica Nanoparticles: Synthesis, Characterization, and Biomedical Uses - Saputra, Ozi Adi; Safitriono, Wahyu Nur; Istiqomah, Annisa; Kumalasari, Meiyanti Ratna; Irmawan, Muhammad; Wibowo, Fajar Rakhman (Universitas Islam Indonesia, 2024)
Mesoporous silica nanoparticles (MSNs) have drawn significant attention due to their exceptional properties and diverse range of applications, particularly in nanomedicine. The distinctive properties of MSNs, such as their high surface area, tunable pore size, and versatile surface chemistry, make them ideal candidates for various biomedical applications. This review aims to present a detailed understanding of MSNs, from synthesis and characterization to their versatile applications in biomedicine, highlighting their significant potential in advancing healthcare technologies. The synthesis methods for MSNs were comprehensively discussed, emphasizing the influence of parameters like solvent, base, alkoxysilane concentrations, and template surfactants on the size and shape of the nanostructures. Different types of MSNs, including MCM-41, SBA-15, KIT-6, and hollow MSNs, are discussed, along with their synthesis protocols and unique characteristics. The review also covers various spectroscopic techniques, such as XRD, XPS, FTIR, NMR, and fluorescence spectroscopy, which are crucial for characterizing MSNs. Furthermore, the biomedical applications of MSNs are highlighted, demonstrating their potential in drug delivery systems, imaging, and diagnostics. The review concludes with a discussion of the future perspectives and challenges in the field, providing insights into potential developments and the prospects for clinical translation.